Parameters of Blood Serum Profiles of Lactating Goats with Different Number of Parturitions - Kumala, Seraphina; Suranindyah, Yustina Yuni; Widayati, Diah Tri (2022)
Background and Objective: The reproductive ability of dairy goats can affect the sustainability of milk supplies which is influenced by the number of parturitions of does. This study aimed to understand the efficiency of the reproductive ability of dairy goats through blood serum parameters of goats with different numbers of parturitions. Materials and Methods: The study used lactating goats with approximate BCS of three which were kept in individual pens under the same circumstances and were divided into three groups based on the rates of parturitions. The blood serum was collected (n = 162) to study the changes in the blood serum parameters in the lactating goats, those with different numbers of parturitions. In addition, this study attended the uniformity of nutrient intake. Results: The blood serum parameters such as glucose, cholesterol, albumin and BUN differ significantly (p<0.05) and decrease if the number of parturitions increases. Conclusion: Regarding glucose, cholesterol, albumin, BUN, creatinine and total protein level, does with parturition one and two were best for nutrient availability to support reproductive activities. Does with parturitions of three and four were still proper to be used for breeding and lactation programs because the parameters of the blood serum profiles were still proper for reproductive activities. © 2022 Seraphina Kumala et al.